Allergic contact dermatitis caused by (meth)acrylates in nail cosmetic products in users and nail technicians - a 5-year study - Raposo, I (2017)
BACKGROUND: The increasing use of long-lasting nail aesthetic products has led to a growing number of cases of allergic contact dermatitis (ACD) caused by (meth)acrylates in recent years. OBJECTIVES: To provide information on ACD caused by (meth)acrylates related to nail cosmetic products. METHODS: We retrospectively reviewed files of patients with ACD caused by (meth)acrylates related to nail cosmetic products, who were patch tested between January 2011 and December 2015 in 13 departments of dermatology in Portugal. RESULTS: Two-hundred and thirty cases of ACD caused by (meth)acrylates (55 technicians, 56 consumers, and 119 with mixed exposure) had been documented, mostly as chronic hand eczema (93%). The most common sensitizers were: 2-hydroxyethyl methacrylate (HEMA), which was positive in 90% of the tested patients, 2-hydroxypropyl methacrylate (HPMA), which was positive in 64.1%, and ethyleneglycol dimethacrylate, which was positive in 54.5%. CONCLUSION: HEMA and HPMA were the most frequent positive allergens. HEMA, which identified 90% of cases, can be considered to be a good screening allergen. The high number of cases of ACD caused by (meth)acrylates in nail cosmetic products certainly warrants better preventive measures at the occupational level, and specific regulation in the field of consumer safety.